International tail risk and World Fear. (May 2019) - Hollstein, Fabian; Nguyen, Duc Binh Benno; Prokopczuk, Marcel; Wese Simen, Chardin
Highlights: International tail risk is highly integrated, motivating a global tail risk index. Both local and global tail risk strongly predict global equity index excess returns. There is a substantial premium for tail risk in the cross-section of countries. Global tail risk is linked to international economic activity. Abstract: We examine the pricing of tail risk in international stock markets. Studying all MSCI Developed and Emerging Markets countries, we find that the tail risk of these countries is highly integrated. We find that both local and our newly computed global tail risk strongly predict global equity index excess returns. These results hold both in-sample and out-of-sample. Sorting countries into portfolios by their tail risk generates sizable excess returns across various holding periods. Finally, we find that global tail risk is linked to international economic activity.